Development of mathematical monopoly game to improve mathematical communication ability - Rosyadi, Alfiani Athma Putri; Wardani, Shafanda Setya; Cholily, Yus Mochamad (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aimed to design and develop a math monopoly board game as a learning tool to boost students’ mathematical communication skills. The motivation for this research comes from the need to improve both written and oral communication abilities in mathematics among middle school students. Method: The research followed a research and development (R&D) approach using the ADDIE model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. The math monopoly game was created and validated by experts in the field, and then tested with eight eighth-grade students from SMP Muhammadiyah 09 Gondanglegi, selected using purposive sampling. Data were collected using validation sheets, questionnaires, and interview guides. The effectiveness of the game was assessed using descriptive statistics and paired sample t-tests to measure students’ mathematical communication before and after the intervention. Findings: The findings showed that the developed monopoly game was highly valid and practical as a learning medium according to both experts and students. Playing the game led to a significant improvement in students’ written mathematical communication, as seen in their increased test scores after using the game. However, there was little change in students’ oral mathematical communication, suggesting that simply playing the game is not enough to foster verbal interaction, and that additional support from teachers during play is important. Significance: This research highlights the potential of game-based learning to make mathematics lessons more engaging and to improve students’ ability to express mathematical ideas in writing. It also points out the need for teacher involvement and further strategies to help students improve their oral communication in mathematics.